Proposed policy for preparation of high-quality primary school teachers in Thailand - Mattavarat, Sutidarat; Viseshsiri, Pongsin; Siribanpitak, Pruet (Kasetsart Journal of Social Sciences, 2017)
Successful countries in education show that the reform process to improve teacher quality begins by answering fundamental questions about the current problems and the needs of the schools. The research objective of this study was to evaluate these answers, describe the current situation and put forward recommendations to policy makers to prepare highquality primary school teachers in Thailand. The study was based on future research design using the methodology of the Ethnographic Delphi Futures Research (EDFR) as a way to reflect the needs of the organizations. Based on the opinions of 160 interviewed participants, 14 experts in education provided consensus ideas for policy development with the aim of improving teacher quality in primary education. All organizations involved in education need to cooperate to set up standards for high-quality primary school teachers. A roadmap is given to set up a new policy.